Sex Differences in the Psychometric Properties of the Pittsburgh Sleep Quality Index - Morris, Jonna L. (J Womens Health (Larchmt), 2018)
Background: The Pittsburgh Sleep Quality Index (PSQI) is a well-known, validated, and reliable instrument used to measure the clinical construct of sleep quality. Little research has been done to measure its psychometric properties by sex. Previous researchers have established the validity of a three-factor structure, but it is unknown whether it applies to both men and women equally. Materials and Methods: This study examined 198 participants; women (n = 104), men (n = 94) who were participants in the Diabetes Sleep Treatment Trial, an ongoing study examining the effect of continuous positive airway pressure on glycemic control in people with type 2 diabetes. A principal components analysis with varimax rotation, scree plots, parallel analysis, and Eigenvalues confidence intervals were all computed to determine factor structure using the seven components measured in the PSQI. Results: Component one, a question about perceived sleep quality, loaded with “sleep efficiency” and “sleep duration” in men and with “daytime dysfunction” and “sleep disturbances” in women. Conclusion: This study confirms a three-factor structure as previously suggested; however, “perceived sleep quality” may load differently depending on the sex being examined. This result suggests that men and women may interpret what is meant by “overall sleep quality” differently.